Contributions of Muhammad Mahfuz Al-Tarmasiy in The Field of Islamic Studies - Hussin, Hayati; Rahim Ahmad, Abdul; Hafiz Saleh, Muhammad; Zainatul Nadra Zainol, Nur; Zakaria, Rohana (International Journal of Engineering and Technology, 2018)
The present study, in principle, aims to introduce an archipelago figure who was once the focus of knowledge seekers in the Holy City of Makkah, Shaykh Muhammad Mahfuz Al-Tarmasiy. This scholar had also left behind significant contributions in his birthplace in Â the Island of Java. To identify his stature in the field of Islamic studies, scholarly works that bring to light the aesthetics of his writings will be briefly highlighted, fitting with the requirements of research papers. The methodology used in the present study is inclined towards qualitative research that encompasses the various sources of information in the form of his writings, be it from published books, untouched original manuscripts, theses and dissertation that look into his manuscripts and books, and the official website of the institution that was established by his successors. Interviews with his grandchildren and great-grandchildren living across the country will also be utilized as one of the methods used in identifying this figure, his background and the general view about his stature. The results of the study found that, al-Tarmasiyâ€™s stature in the area of Islamic studies is indeed superior based on two factors: First: The establishment of traditional and modern educational institutions in Java that were inspired by his enthusiasm and struggles for the sake of knowledge. Second: The impact of his meticulous works that span over twenty books on the academic world and on the traditional talaqqi education system.Â